2016
DOI: 10.1371/journal.pone.0162590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diclofenac, L-NAME, L-Arginine, and Pentadecapeptide BPC 157 on Gastrointestinal, Liver, and Brain Lesions, Failed Anastomosis, and Intestinal Adaptation Deterioration in 24 Hour-Short-Bowel Rats

Abstract: Stable gastric pentadecapeptide BPC 157 was previously used to ameliorate wound healing following major surgery and counteract diclofenac toxicity. To resolve the increasing early risks following major massive small bowel resectioning surgery, diclofenac combined with nitric oxide (NO) system blockade was used, suggesting therapy with BPC 157 and the nitric oxide synthase (NOS substrate) L-arginine, is efficacious. Immediately after anastomosis creation, short-bowel rats were untreated or administered intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 36 publications
5
88
0
Order By: Relevance
“…Results of this field study demonstrated that BPC 157 administrated via sugar syrup as a food supplement significantly reduced ( (Klicek et al, 2013;Lojo et al, 2016;Sikiric et al, 2001;Veljaca et al, 1995). As indicated previously, BPC 157 has been tested in clinical trials as an agent against ulcerative colitis, but studies have shown its efficacy throughout complete gastrointestinal tract .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Results of this field study demonstrated that BPC 157 administrated via sugar syrup as a food supplement significantly reduced ( (Klicek et al, 2013;Lojo et al, 2016;Sikiric et al, 2001;Veljaca et al, 1995). As indicated previously, BPC 157 has been tested in clinical trials as an agent against ulcerative colitis, but studies have shown its efficacy throughout complete gastrointestinal tract .…”
Section: Discussionmentioning
confidence: 91%
“…Finally, the conclusive prospect (i.e., BPC 157 application as an innate treatment to successfully oppose invasion with N. ceranae ) is supported by a variety of beneficial effects of BPC 157 noted in colitis lesion studies (Klicek et al., ; Lojo et al., ; Sikiric et al., ; Veljaca et al., ). As indicated previously, BPC 157 has been tested in clinical trials as an agent against ulcerative colitis, but studies have shown its efficacy throughout complete gastrointestinal tract (Sikiric et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…We noted the antagonization of the corresponding alcoholinduced [48][49][50][51][52] and NSAIDs-induced [53][54][55][56][57] stomach lesions, much like the counteraction of the liver and brain lesions, which were induced by alcohol [58][59][60] or NSAIDs. [53][54][55][56][57]61 To emphasize, much like the prototypic acute alcohol-stomach lesion, [48][49][50][51] the beneficial range of the BPC 157 counteracts alcohol in both acute intoxication (protracted drowsiness, increased alcohol level in blood, hypothermia) and chronic intoxication (withdrawal convulsions). 59,60 Likewise, it counteracts consequences of the chronic abuse (drinking alcohol for 3 months) 58 such as chronic gastric lesions 51 or liver lesions with portal hypertension.…”
Section: Original Robert's Cytoprotection/adaptive Cytoprotection/ Ormentioning
confidence: 99%
“…58 For NSAIDsadverse effects (i.e., gastrointestinal, liver and brain injuries), BPC 157 counteraction includes both COX-1 and COX-2 block-ers. [52][53][54][55][56][57]61 BPC 157 reduces bleeding after amputation, and may also counteract aspirin induced prolongation of bleeding and thrombocytopenia. 62,63 An interesting point is that BPC 157 may also prevent and reverse adjuvant arthritis in rats.…”
Section: Original Robert's Cytoprotection/adaptive Cytoprotection/ Ormentioning
confidence: 99%
See 1 more Smart Citation